Biblioverse Tok Bayu Edu: bridging social and emotional learning through digital bibliotherapy for sustainable education - Norul Azizi, Nur Dayana Balqis; Ahmad, Masitah; Hussin, Norhayati; Abdul Aziz, Rafidah (2025)
This BIBLIOVERSE TOK BAYU EDU is an all-in-one digital bibliotherapy platform that integrates emotional literacy, cultural wisdom, and technology for sustainable emotional learning. Aimed at educational settings and underserved communities, it supports stigma-free mental wellness aligned with SDGs 3, 4, and 10. The platform of ers AI-guided mood check-ins, personalized content, and a rich Emotional Library of books, fan fiction, videos, music, podcasts, and games curated based on users' feelings. Through Bayu Academy, users explore microlearning modules on empathy, conflict resolution, emotional intelligence, and healing, earning certificates, XP, and badges along the way. It's supported by BiblioBot, a chat companion guiding journaling and reflection. Healing is gamified: players complete BiblioBot Quests, gain Emotional XP, and unlock titles like Empathy Mage or Bayu Guardian. With the Bayukit Builder, users craft their emotional survival toolkit, blending journaling, quotes, music, and reflections logged on their Achievement Board. Safe emotional expression is fostered in moderated spaces, such as the Grief Café and the Joy Zone. Ethical AI ensures content moderation, trigger warnings, and trauma-sensitive filters. Accessibility is core, featuring multilingual options, readable fonts, haptic feedback, sign language avatars, and voice-to-text tools. TOK BAYU reimagines emotional education as a right, not a privilege. By merging emotional learning with technology and storytelling, it empowers students, educators, and youth to build lifelong emotional resilience in an inclusive, future-ready ecosystem.